2019
DOI: 10.1186/s12984-019-0585-x
|View full text |Cite
|
Sign up to set email alerts
|

Retraining walking over ground in a powered exoskeleton after spinal cord injury: a prospective cohort study to examine functional gains and neuroplasticity

Abstract: BackgroundPowered exoskeletons provide a way to stand and walk for people with severe spinal cord injury. Here, we used the ReWalk exoskeleton to determine the training dosage required for walking proficiency, the sensory and motor changes in the nervous system with training, and the functionality of the device in a home-like environment.MethodsParticipants with chronic (> 1 yr) motor complete or incomplete spinal cord injury, who were primarily wheelchair users, were trained to walk in the ReWalk for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 64 publications
(70 reference statements)
0
72
0
Order By: Relevance
“…Reduced spasticity following exoskeleton training in SCI patients has been reported in previous studies. 17 19 27 28 Mirbagheri et al 29 reported that robotic-assisted gait training in SCI patients reduced spasticity by modulation of intrinsic joint properties and stretch reflex stiffness. The reduction in spasticity in this study might be explained by the fact that the exoskeleton enables chronic SCI patients to perform bipedal ambulation and move through the normal range of motion of multiple lower extremity joints.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced spasticity following exoskeleton training in SCI patients has been reported in previous studies. 17 19 27 28 Mirbagheri et al 29 reported that robotic-assisted gait training in SCI patients reduced spasticity by modulation of intrinsic joint properties and stretch reflex stiffness. The reduction in spasticity in this study might be explained by the fact that the exoskeleton enables chronic SCI patients to perform bipedal ambulation and move through the normal range of motion of multiple lower extremity joints.…”
Section: Discussionmentioning
confidence: 99%
“…In patients without (the potential for) ambulatory capacity (i.e., complete SCI), who are wheelchair users for their mobility, an exoskeleton can be used as an assistive device in order to walk. However, exoskeleton use as an assistive device without physical assistance from a trainer requires an intensive training period 7 9 . In our previous study, we have shown that more than half of the participants with a complete SCI could use an exoskeleton independent of assistance under supervision of a buddy after 24 training sessions 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of an exoskeleton for gait restoration was demonstrated by improving unassisted gait speed and walking distance after exoskeleton training 6 . Furthermore, two non-walkers with an incomplete SCI became walkers after exoskeleton training 4,7 . Hence, for people with incomplete SCI, 'therapeutic' exoskeleton use has the potential to improve ambulatory capacity independent of the exoskeleton.…”
mentioning
confidence: 99%
“…Functional improvements were reported, especially in people with incomplete injuries. Spasticity had mixed changes, suggesting differences between high versus low spasticity prior to training [88].…”
Section: Robotic Exoskeletonsmentioning
confidence: 99%